Faktor-Faktor Yang Berhubungan Dengan Pemanfaatan Pelayanan Kesehatan Gigi Pada Peserta Bpjs Di Puskesmas Setabelan Kota Surakarta - Khoiriyah, Rizqiyani; , Kusuma Estu Werdani S.KM., M.Kes (2017)
Utilization of dental health services still need to be considered by the participants BPJS. Participants of BPJS have the right to utilize their dental health services curative or preventive measures. This study aims to determine the associated factors with the utilization of health services, namely dental health knowledge, dental health conditions, services access, and satisfaction of dental health services at Local Government Clinic Setabelan. The research type is quantitative analytic with Crossectional approach. The population in this study were all recorded BPJS' participants at Local Government Clinic Setabelan as many as 125 respondents. Data were taken using Accidental sampling technique. The data analysis is Chi-Square test. This research was conducted on May 9th - 13th of May 2017. The result of this research is unrelated variable that is utilization of dental health service with dental health knowledge (p value 0,305), utilization of dental health service with dental health condition (p value 1,000), utilization of dental service with service access (p value 0,545), And utilization of dental services with dental health services (p value 0,230). The conclusion of the research is there is no correlation of knowledge of dental health, dental health condition, service access and dental health service satisfaction with utilization of dental health service by BPJS' participants at local government clinic Setabelan Year 2017.